(untitled) (Medico Legal Update, 2021)
Excessive ethanol intakes have been reported to be linked to liver diseases such as hepatitis and cancerrelated diseases of ethanol. Excessive ethanol can lead to the accumulation of reactive oxygen species (ROS) and to the depletion of glutathione (GSH) in the liver. Ethanol-induced oxidative stress substantially increases peroxidation of the lipid and decreases GSH levels in human hepatocyte and animal models. Ethanol contributes to sterol regulating element-binding protein activation (SREBP)-1 by regulating main genes such as Acetyl-CoA carboxylase (ACC) and Stearoyl-CoA desaturase 1(SCD1) to facilitate lipid accumulation in the liver. The liquid fraction derived from wolfberry is lycium barbarum polysaccharide (LBP). In many animal disease models, it is an effective antioxidant and tissue protective agent. Researchers have shown hepato-protective functions in acute hepatic injury, NAFLDs, drugs-induced liver injury and hepatocellularcarcinoma models. The protection effect of L. barbarum polysaccharides (LBP) in this study on ethanol-induced injury in human hepatocytes was explored. In addition, the influence of LBP on oxidative stress protein activity was examined.